THE DYNAMICS OF CHILD DEVELOPMENT IN THE PERSPECTIVE OF ISLAMIC EDUCATIONAL PSYCHOLOGY - Wadham, Ben; Mansir, Firman (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This article aimed to explain the importance of Islamic educational psychology's role in child development. Psychological development in children varies. Some developments are excellent and appropriate, while others are not and have not been fulfilled. Psychological development in children that has been fulfilled includes emotional development and the ability to read and write. Meanwhile, psychological development and moral development have not been fulfilled. The role of Islamic educational psychology is crucial in child development so that Islamic educational psychology can be accessed in shaping children's attitudes and souls through instilling awareness that has a relationship with personal inner values. The method used in this study was a qualitative approach, with data collected through a descriptive-analytical literature review analysis. This research shows that children's development can grow through spiritual and social approaches in a dynamic learning process. Therefore, child development in the context of their lives can change according to the family, school, and community environments.